Additional procedures for characterizing the performance of recycled polymer modified asphalt mixtures. (January 2022) - Viscione, Nunzio; Veropalumbo, Rosa; Oreto, Cristina; Biancardo, Salvatore Antonio; Abbondati, Francesco; Russo, Francesca
Highlights: Asphalt mixtures characterization. Measurement procedures and techniques for modified asphalt mixtures characterization. Unmodified mixture is compared to those modified via dry and wet processes. Best mixing and compaction processes for achieving the same volumetric properties. Dry process caused the best performance in terms of water sensitivity. Abstract: Great efforts have been made in recent years to improve the mechanical properties of asphalt mixtures by replacing conventional mix components with innovative ones or by adding materials such as polymers. Hence, the innovative-sustainable road materials to be investigated through laboratory tests require articulated procedures, the research here presented aims to provide an experimental-methodological approach to analyse the mechanical performance of untraditional hot asphalt mixtures made up using a polymer compound of recycled plastics. Three Asphalt Concrete 20 (AC20) Hot Asphalt Mixtures (HMA) were analysed by measuring base properties (i.e., indirect tensile strength and moisture damage) and advanced features (i.e., stiffness, fatigue, cracking and rutting resistance). As a result, the addition of polymer compound using dry process might lead firstly to change the laboratory mixing procedure than the traditional hot limestone asphalt solutions. The main benefits derived from the adoption of this innovative technology compared to the conventional ones are as follows: a) an improvement of resistance to moisture damage (at 15 °C); b) a suitable stiffness at 10, 20 and 40 °C; c) an increment of the cracking resistance (at 10 °C) and d) a good rutting resistance in terms of rut depth (at 60 °C). .